The Use of Output-Based Aid in Small Scale Irrigation Schemes in Developing Countries - World Bank (Washington, DC, 2014)
This report has been completed to explore the use of output-based aid (OBA) as a financing mechanism to support the development and operation of small-scale irrigation schemes in developing countries. The specific objectives of the report were to: evaluate the scope for OBA in financing small-scale irrigation schemes to support poor farmers in developing countries and propose project design and implementation arrangements, based on real-world examples, to support sustainable small scale irrigation schemes benefiting from OBA, either under public or private management. The aim is being to provide recommendations on the appropriate next steps for using OBA subsidies to support the implementation of projects in the irrigation sector.